Emotions, Alexithymia, and Emotion Regulation in Patients With Psoriasis - Panasiti, Maria Serena; Ponsi, Giorgia; Violani, Cristiano (Frontiers in Psychology, 2020)
Psoriasis is a chronic dermatological condition which is frequently associated with problematic patterns of emotional reactivity (the way in which patients reacts to stimuli), alexithymia (their ability to recognize and label the emotional reaction) and emotion regulation (the ability to enhance or reduce one’s own emotional reaction). A research in the peer-reviewed scientific literature was conducted in order to identify articles describing the association of psoriasis and affective problems. In particular, we first evaluate studies that have investigated abnormal emotional reactivity (in terms of duration, frequency or type of the experienced emotions) and its impact on patients’ quality of life; next, we review the role of alexithymia and emotion regulation in modulating the relationship between emotional reactivity and quality of life in this population. From a critical analysis of the reviewed studies, we highlight that altered emotional processing might be particularly important in the characterization of this condition. In particular we show that this condition is related with an emotional reactivity characterized by negative emotions that has a stronger impact on patients’ quality of life when emotion regulation abilities are weak, especially if patients have alexithymia. Finally, we present suggestions for future directions in both clinical and research fields.